Social Entrepreneur Sebagai Core Competence, Tinjauan dari Marketing Perspective - Zuchroh, Imama (Akutansi Bisnis & Manajemen ( ABM ), 2016)
Long term purpose of this research is to widely spread the theme of Social Entrepreneur. The Social Entrepreneur Model is a unique concept as it combines two contrast concepts which are "Social" and "Entrepreneur". "Social" is inclined to social term with less profit oriented; whereas "Entrepreneur" has a tendency to a profit oriented condition. Specific purpose of this paper is to analyse the Core Competence of Pelangi Nusantara Community, viewed from Marketing Perspective. There are three basic variables of Core Competence: (1) It is a source of competitive advantage in that it makes a significant contribution to perceived customer benefit; (2) It has a potential breadth of applications to a wide variety of markets; and (3) It is difficult for competitors to imitate (Kotler, 2002). Qualitative Research was conducted. Very strong core competence from the three variables has been attained by Pelangi Nusantara Community, and this leads to toughen the Pelangi Nusantara Marketing Strategy.